THE LEGITIMACY OF POWER AND THE REVOLUTION - V. А. Glukhikh; S. M. Eliseev (Дискурс, 2016)
The article is devoted to the problem of the revolution impact on the government legitimacy. Revolutions in modern times have become a synonym of a legitimate way of overthrowing the existing government. If in previous historical era in politics the people´s right to riots and uprisings was denied, the current policy recognizes their right to revolution. Without recognition of this right, the revolution is not only deprived of legitimacy, but also the institutions which arise in the process of its implementation lose credibility.